ANALISIS PELAYANAN PRIMA PADA KANTOR PT.PLN (PERSERO) MELAK KABUPATEN KUTAI BARAT - Astiah Safari, Maskan AF, dan Salasiah (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2022)
This research was conducted with the aim of knowing the application of excellentservice at the Office of PT. PLN (Persero) Melak, West Kutai Regency in implementingexcellent service standards and processes. This research itself is a qualitative descriptivetype. The focus of this research is attitude (Attitude), ability (Ability), attention (Attention),action (Action), and responsibility (Accountability) in the Office of PT. PLN (Persero)Melak West Kutai Regency.Based on the results of research, and discussion of the application of excellentservice in the Office of PT. PLN (Persero) Melak West Kutai Regency is good. Based onthe attitudes, abilities, attention, actions, and responsibilities carried out by the employeesof the PT. PLN (Persero) Melak West Kutai Regency can be seen that it has been carriedout optimally. However, there are still indicators that are considered not optimal, such asdelays in employee response in serving the community who provide services through socialmedia and inadequate parking lots, especially parking for four-wheeled vehicles.